Radiological Manifestation of Progressive Massive Fibrosis as a Complication of Silicosis-Case Report - Sharma, Bharat Bhusan; Mishra, Dhiraj Kumar; Singh, Tanu; Nargotra, Natasha; Sharma, Rohit Kumar; Gupta, Puneet (Nepalese Journal of Radiology, 2020)
Progressive massive fibrosis (PMF) is the outcome of complicated silicosis and falls in the category of occupational lung diseases. The underlying etiological factors responsible for this are fine particles of silica, inhaled by workers in certain specific occupation. We present a 42-year-old male patient with chief complaint of breathlessness and had occupational background in relation to sandblasting. HRCT chest had shown confluent fibrotic densities in bilateral upper lobes with loco regional bronchietatic changes and adjacent pleural thickening. The patient was diagnosed of having PMF on the history and classical HRCT findings